2013
DOI: 10.1017/s2040174413000342
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin D deficiency programmes adult renal renin gene expression and renal function

Abstract: Renin is essential for renal development and in adult kidneys vitamin D deficiency increases renin gene expression. We aimed to determine whether maternal vitamin D deficiency upregulates fetal renal renin expression, and if this is sustained. We also examined growth and the long-term renal effects in offspring on a normal diet. Female Sprague-Dawley rats in UVB-free housing were fed either vitamin D deficient chow (DEF) or normal chow from 4 weeks and mated with vitamin D replete males at 10 weeks. Fetuses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…Although offspring nephron number was increased by maternal vitamin D deficiency, these additional nephrons could be abnormal. Boyce et al (2013) found that adult male offspring of vitamin D deficient dams who ate normal chow from weaning had a reduced creatinine clearance and others have reported high blood pressure and ventricular hypertrophy in young offspring maintained on a vitamin D deficient diet ( Gezmish et al, 2010 ; Tare et al, 2011 ).…”
Section: Abnormal Renal Developmentmentioning
confidence: 99%
“…Although offspring nephron number was increased by maternal vitamin D deficiency, these additional nephrons could be abnormal. Boyce et al (2013) found that adult male offspring of vitamin D deficient dams who ate normal chow from weaning had a reduced creatinine clearance and others have reported high blood pressure and ventricular hypertrophy in young offspring maintained on a vitamin D deficient diet ( Gezmish et al, 2010 ; Tare et al, 2011 ).…”
Section: Abnormal Renal Developmentmentioning
confidence: 99%
“…Vitamin D deficiency in rats during the nephrogenic period leads to renal disorders in adulthood, such as a 20% increase in glomerular numbers, associated with a significant reduction in renal corpuscle volume [126,132]. Maternal vitamin D deficiency leads to elevated fetal renal renin mRNA level and this persists in adulthood, associated with impaired renal function [133]. Vitamin D deficiency in rats during renal development causes disturbances in renal microvasculature that are persistent in adulthood, accompanied by increased plasma levels of ANGII.…”
Section: Impact Of Environmental Factors On Renin-angiotensin System mentioning
confidence: 99%
“…Vit.D-pups also had lower BWs, confirming the results of previous studies. 11 However, these rats presented with a higher BW compared with the CG group in adulthood. Wen et al demonstrated that Vit.D deficiency during pregnancy stimulates the proliferation and differentiation of pre-adipocytes, which may be associated with the alteration in the methylation of genes, such as Vldlr and Hif1α, leading to offspring obesity.…”
Section: Discussionmentioning
confidence: 84%
“…Vessel rarefaction in the medulla, which is associated with increased ANGII due to renal development disorders, may have contributed to the changes in urinary concentration. 20,11 It has been shown that ANGII increases differentiation and branched ureteric buds in vivo and is responsible for renal vessel formation during kidney development. 9 Increased ANGII during renal development can lead to imbalanced angiogenesis factors for vascular branches, which impairs renal vessel maturation, promotes arteriolar wall thickening and reduces inner medulla volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation